Health, wellbeing, and disability among older people infected or affected by HIV in Uganda and South Africa - Makandwe Nyirenda; Marie-Louise Newell; Joseph Mugisha; Portia C. Mutevedzi; Janet Seeley; Francien Scholten; Paul Kowal (Global Health Action, 2013)
Objective: To describe and compare the health status, emotional wellbeing, and functional status of older people in Uganda and South Africa who are HIV infected or affected by HIV in their families. Methods: Data came from the general population cohort and Entebbe cohort of the Medical Research Council/Uganda Virus Research Institute, and from the Africa Centre Demographic Information System through cross-sectional surveys in 2009/10 using instruments adapted from the World Health Organization (WHO) Study on Global Ageing and adult health (SAGE). Analysis was based on 932 people aged 50 years or older (510 Uganda, 422 South Africa). Results: Participants in South Africa were slightly younger (median age − 60 years in South Africa, 63 in Uganda), and more were currently married, had no formal education, were not working, and were residing in a rural area. Adjusting for socio-demographic factors, older people in South Africa were significantly less likely to have good functional ability [adjusted odds ratio (aOR) 0.72, 95% CI 0.53–0.98] than those in Uganda, but were more likely to be in good subjective wellbeing (aOR 2.15, 95% CI 1.60–2.90). South Africans were more likely to be obese (aOR 5.26, 95% CI 3.46–8.00) or to be diagnosed with hypertension (aOR 2.77, 95% CI 2.06–3.73). Discussion and conclusions: While older people's health problems are similar in the two countries, marked socio-demographic differences influence the extent to which older people are affected by poorer health. It is therefore imperative when designing policies to improve the health and wellbeing of older people in sub-Saharan Africa that the region is not treated as a homogenous entity.